Parallel composite fiber and preparation method thereof
By adding elastic bodies to the first group of parallel composite fibers and adding nuclear doses to the second group, the difference between the two groups is increased, and the problem of high production cost of parallel composite fibers has been solved. High elastic, low -cost fiber preparation.
Patent Information
- Application Number
- CN202310066726.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-01-12
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2043-01-12
AI Technical Summary
The production cost of existing parallel composite fibers is high, which leads to easy peeling during spinning and difficult to carry out.
The regenerative polyester with different viscosity is used as the raw material. By adding elastic body to the first group to increase its elasticity, adding a nuclear agent to the second group to increase its rigidity, and increase the difference between the two groups. The curling effect of composite fiber.
A composite fiber with a higher production cost, better elasticity, and higher fluffy filling has a better breakdown and elongation rate. The rolling elasticity rate is generally more than 80 %.
Smart Images

Figure BDA0004073593010000171
Abstract
Description
Technical Field
[0001] The present application belongs to the technical field of composite fibers, and in particular, relates to a parallel composite fiber and a preparation method thereof. Background Art
[0002] In recent years, clothing, pillows, and dolls that use parallel composite fibers as fillings are becoming more and more popular due to their advantages such as good fluffiness, high elastic recovery rate, washability, and durability. The curling characteristics of traditional chemical fibers are obtained through mechanical winding and thermal processing. This type of curling is generally a flat serrated shape, with the disadvantages of unstable curling structure, poor elastic recovery, and poor durability. The curling structure of parallel composite fibers is caused by the different shrinkage amounts of its different components after mechanical processing and heat treatment. This bending structure is permanent and stable, and different curling effects and performance can be achieved by adjusting the components and proportions in the composite fibers.
[0003] However, the parallel composite fiber relies on the adhesion between the two components to maintain the parallel composite structure, which makes it easy to peel off during the spinning process, making the spinning process difficult, which also causes the production cost of parallel composite fibers to be higher than that of ordinary fibers. Summary of the invention
[0004] The purpose of the present application is to provide a parallel composite fiber and a preparation method thereof, aiming to solve the problem of high production cost of existing parallel composite fibers.
[0005] In order to achieve the above application purpose, the technical solution adopted in this application is as follows:
[0006] In a first aspect, the present application provides a parallel composite fiber, comprising: a first component and a second component, wherein the first component comprises a first regenerated polyester and an elastomer, and the second component comprises a second regenerated polyester and a nucleating agent, and the viscosity of the melt of the first regenerated polyester is lower than the viscosity of the melt of the second regenerated polyester.
[0007] Optionally, the intrinsic viscosity of the first recycled polyester is 0.65 dL / g to 0.75 dL / g.
[0008] Optionally, the intrinsic viscosity of the second recycled polyester is 0.67 dL / g to 0.80 dL / g.
[0009] Optionally, the first recycled polyester includes at least one of bottle flakes obtained from waste PET bottles, friction materials obtained from waste PET films, waste PET yarns, waste PET textiles or / and waste PET clothing, and foam materials obtained from waste PET films, waste PET sheets, waste PET yarns, waste PET textiles or / and waste PET clothing.
[0010] Optionally, the second recycled polyester includes bottle flakes obtained by recycling waste PET bottles and / or a solid phase viscosity-increasing material of bottle flakes.
[0011] Optionally, the mass ratio of the first component to the second component is (40-50):(60-50).
[0012] Optionally, in the first component, the mass ratio of the first recycled polyester to the elastomer is (60-99):(40-1).
[0013] Optionally, the elastomer includes at least one of styrene-based thermoplastic elastomers, thermoplastic polyurethanes, thermoplastic polyolefin elastomers, polyethylene-polyvinyl acetate elastomers, polyamide elastomers, polyethylene terephthalate-polyethylene glycol block copolymers, and polyethylene terephthalate-1,4-cyclohexanedimethanol ester.
[0014] Optionally, the first component further includes a compatibilizer, and the added amount of the compatibilizer is 1 wt% to 10 wt% of the total mass of the first component.
[0015] Optionally, the compatibilizer is prepared by grafting a grafting monomer onto a polyolefin or a polyolefin elastomer, and the grafting monomer includes at least one of maleic anhydride and glycidyl methacrylate (GMA).
[0016] Optionally, the elastomer includes the polyethylene terephthalate-1,4-cyclohexanedimethanol ester and the polyethylene terephthalate-polyethylene glycol block copolymer, and the mass ratio of the polyethylene terephthalate-polyethylene glycol block copolymer to the polyethylene terephthalate-1,4-cyclohexanedimethanol ester is (0.05-0.4).
[0017] Optionally, in the second component, the mass proportion of the nucleating agent is 0.1 wt% to 3 wt%.
[0018] Optionally, the nucleating agent is an inorganic nucleating agent, and the inorganic nucleating agent includes at least one of ZnO, MgO, Al2O3, Fe2O3, SiO2, BaSO4, Na2CO3, NaHCO3, CaCO3, carbon black, graphite, zinc powder, aluminum powder, talcum powder, halloysite, carbon nanotubes, montmorillonite, metal-organic framework materials and pyrophyllite.
[0019] Optionally, the second component further comprises an ionic liquid, the ionic liquid is adsorbed on the nucleating agent, and the added amount of the ionic liquid is 0.1 wt% to 5 wt% of the total mass of the nucleating agent.
[0020] Optionally, the ionic liquid includes at least one of 1-allyl-3-methylimidazole chloride, 1-butyl-4-methylpyridinium hexafluorophosphate, 2-methylimidazole, 2-bromoisobutyryl bromide, N-butyl-4-methylpyridinium hexafluorophosphate, 1-tetradecyl-3-methylimidazole bromide, and 1-dodecyl-3-methylimidazole chloride.
[0021] Optionally, the morphology of the inorganic nucleating agent includes at least one of tubular, rod-shaped, sheet-shaped, spiral-shaped and granular.
[0022] Optionally, the particle size of the inorganic nucleating agent is 450nm to 550nm.
[0023] Optionally, the metal-organic framework material includes at least one of ZIF-8, ZIF-67, MIL-53, MIL-100 and MIL-101.
[0024] In a second aspect, the present application provides a method for preparing the above-mentioned parallel composite fiber, comprising:
[0025] Providing a premix of the first component, and subjecting the premix of the first component to melt extrusion to obtain a first melt;
[0026] Providing a premix of the second component, and subjecting the premix of the second component to melt extrusion to obtain a second melt;
[0027] The first melt and the second melt are subjected to composite spinning to obtain parallel composite fiber precursors;
[0028] The parallel type composite fiber precursor is post-processed to obtain the parallel type composite fiber.
[0029] Optionally, the composite spinning process includes: metering the first melt and the second melt separately and entering the spinning assembly for spinning, and then ejecting them through a parallel composite spinneret assembly.
[0030] Optionally, in the spinning assembly, a viscosity ratio of the first melt to the second melt is 1:(1-1.2).
[0031] Optionally, the post-treatment includes: subjecting the parallel type composite fiber precursor to water mist spraying, ring-blown air cooling, oiling and stretching to form primary fibers, and then subjecting the parallel type composite fiber precursor to bundling, post-stretching, curling, shaping and cutting to form the parallel type composite fiber.
[0032] Optionally, the spray speed of the water mist is 3.8m / s to 4.0m / s, and the water temperature is 24°C to 26°C.
[0033] Optionally, the ring-blowing wind speed of the ring-blowing cooling is 2.0 m / s to 2.8 m / s, and the wind temperature is controlled at 21° C. to 23° C.
[0034] Optionally, the post-stretching drawing speed is 200m / min to 240m / min.
[0035] Optionally, the winding speed of the curling spinning is 1300m / min to 1700m / min.
[0036] The parallel composite fibers provided in the first aspect of the present application use recycled polyesters of different viscosities as raw materials. By adding an elastomer to the first component, the elongation of the component when subjected to force can be increased, thereby improving the elasticity of the first recycled polyester with relatively low viscosity. By adding a nucleating agent to the second component, the crystallinity of the second recycled polyester with relatively high viscosity can be increased to enhance its rigidity, thereby expanding the difference in shrinkage of different components after mechanical processing and heat treatment, and further enhancing the curling effect of the parallel composite fibers, thereby obtaining a high-elastic filling composite fiber with lower production cost, better elasticity, and higher fluffiness.
[0037] In the preparation method of the parallel composite fiber provided in the second aspect of the present application, the first component includes a first recycled polyester and an elastomer; the second component includes a second recycled polyester and a nucleating agent; the first component and the second component are subjected to a composite spinning process to obtain a composite fiber with a parallel structure. The present application specifically adds an elastomer to the first component to improve its elasticity, adds a nucleating agent to the second component to improve its rigidity, increases the difference between the two components, and strengthens the three-dimensional curling resilience of the parallel composite fiber, so that the fiber has good breaking strength and breaking elongation, and the curling elasticity is generally above 80%, with good fluffiness, washability and durability. DETAILED DESCRIPTION
[0038] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present application more clearly understood, the present application is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.
[0039] In this application, the term "and / or" describes the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone. A and B can be singular or plural. The character " / " generally indicates that the associated objects are in an "or" relationship.
[0040] In this application, "at least one" means one or more, and "plurality" means two or more. "At least one of the following" or similar expressions refers to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b, or c", or "at least one of a, b, and c" can all mean: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, c can be single or multiple, respectively.
[0041] It should be understood that in the various embodiments of the present application, the size of the serial numbers of the above-mentioned processes does not mean the order of execution, some or all of the steps can be executed in parallel or sequentially, and the execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of the present application.
[0042] The terms used in the embodiments of the present application are only for the purpose of describing specific embodiments, and are not intended to limit the present application. The singular forms "a", "said" and "the" used in the embodiments of the present application and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.
[0043] The weight of the relevant components mentioned in the embodiment description of the present application can not only refer to the specific content of each component, but also represent the proportional relationship between the weights of the components. Therefore, as long as the content of the relevant components is proportionally enlarged or reduced according to the embodiment description of the present application, it is within the scope disclosed in the embodiment description of the present application. Specifically, the mass described in the embodiment description of the present application can be a mass unit known in the chemical industry such as μg, mg, g, kg, etc.
[0044] The terms "first" and "second" are used only for descriptive purposes to distinguish objects such as substances from each other, and should not be understood as indicating or implying relative importance or implicitly indicating the number of indicated technical features. For example, without departing from the scope of the embodiments of the present application, the first XX may also be referred to as the second XX, and similarly, the second XX may also be referred to as the first XX. Thus, features defined as "first" and "second" may explicitly or implicitly include one or more of the features.
[0045] The term "PET" is an abbreviation for "Polyethylene terephthalate", which means polyethylene terephthalate.
[0046] The first aspect of the embodiment of the present application provides a parallel composite fiber, which includes a first component and a second component. The first component includes a first recycled polyester and an elastomer, and the second component includes a second recycled polyester and a nucleating agent. The viscosity of the melt of the first recycled polyester is lower than the viscosity of the melt of the second recycled polyester.
[0047] Side-by-side composite fiber refers to a composite fiber in which two component polymers are arranged on both sides of the fiber along the longitudinal direction of the fiber. It is usually required that the interface between the two components has a certain adhesion to avoid interface peeling.
[0048] Recycled polyethylene terephthalate (R-PET) is a material made by recycling plastic products.
[0049] Elastomers are polymers that have elastic properties and can return to their original shape after the external force is removed. Elastomers include but are not limited to thermoplastic elastomers.
[0050] Nucleating agent refers to a functional chemical additive that can change part of the crystallization behavior, improve the transparency, rigidity, surface gloss, impact toughness and heat deformation temperature of the product, shorten the product molding cycle, and improve the processing and application performance of the product.
[0051] The viscosity of the melt of the first recycled polyester is different from that of the melt of the second recycled polyester. Specifically, under the same conditions, the viscosity of the melt of the first recycled polyester is lower than that of the melt of the second recycled polyester, that is, compared with the viscosity of the melt of the second recycled polyester, the viscosity of the melt of the first recycled polyester is relatively low, and the viscosity of the melt of the second recycled polyester is relatively high. The same conditions include but are not limited to the same temperature. Viscosity can also be called viscosity, which refers to the resistance of a fluid to flow.
[0052] The parallel composite fibers provided in the first aspect of the embodiments of the present application use recycled polyesters of different viscosities as raw materials. By adding an elastomer to the first component, the elongation of the component when subjected to force can be increased, thereby improving the elasticity of the first recycled polyester with relatively low viscosity. Adding a nucleating agent to the second component can increase the crystallinity of the second recycled polyester with relatively high viscosity to enhance its rigidity, expand the difference in shrinkage of different components after mechanical processing and heat treatment, and further enhance the curling effect of the parallel composite fibers, thereby obtaining a high-elasticity filling composite fiber with lower production cost, better elasticity, and higher fluffiness.
[0053] In some embodiments, the intrinsic viscosity of the first recycled polyester is 0.65 dL / g to 0.75 dL / g. Intrinsic viscosity is the most commonly used method for expressing the viscosity of a polymer solution, which is the reduced viscosity when the concentration of the polymer solution tends to zero. As an example, the intrinsic viscosity of the first recycled polyester can be, for example but not limited to, any one of 0.65 dL / g, 0.66 dL / g, 0.67 dL / g, 0.68 dL / g, 0.69 dL / g, 0.7 0 dL / g, 0.71 dL / g, 0.72 dL / g, 0.73 dL / g, 0.74 dL / g, 0.75 dL / g or a range of any two thereof.
[0054] In some embodiments, the intrinsic viscosity of the second recycled polyester is 0.67 dL / g to 0.80 dL / g. As an example, the intrinsic viscosity of the second recycled polyester can be, for example but not limited to, any one of 0.67 dL / g, 0.68 dL / g, 0.69 dL / g, 0.70 dL / g, 0.71 dL / g, 0.72 dL / g, 0.73 dL / g, 0.74 dL / g, 0.75 dL / g, 0.76 dL / g, 0.77 dL / g, 0.78 dL / g, 0.79 dL / g, and 0.8 dL / g, or a range of any two thereof.
[0055] In some embodiments, the first recycled polyester includes at least one of bottle flakes obtained from waste PET bottles, friction materials obtained from waste PET films, PET waste yarns, waste PET textiles or / and waste PET clothing, and foam materials obtained from waste PET films, waste PET sheets, PET waste yarns, waste PET textiles or / and waste PET clothing. Optionally, the first recycled polyester only includes bottle flakes, friction materials or foam materials. Optionally, the first recycled polyester includes bottle flakes and friction materials. Optionally, the first recycled polyester includes bottle flakes, friction materials and foam materials. Optionally, the first recycled polyester includes friction materials and foam materials. Optionally, the first recycled polyester includes bottle flakes and foam materials. By designing the first recycled polyester to include bottle flakes, friction materials and / or foam materials, it helps to improve the problem that R-PET with low viscosity is difficult to use for spinning due to poor performance, and at the same time can reduce the cost of raw material procurement, promote the recycling of waste polyester materials, and alleviate environmental pressure.
[0056] In some embodiments, the second recycled polyester includes bottle flakes and / or solid phase thickening materials of bottle flakes obtained by recycling waste PET bottles. Solid phase thickening refers to the condensation polymerization reaction of the flakes in a solid phase state to increase the molecular weight of the flakes and improve the intrinsic viscosity.
[0057] In some embodiments, the intrinsic viscosity of the bottle flakes is 0.77 dL / g to 0.90 dL / g. As an example, the intrinsic viscosity of the bottle flakes can be, for example but not limited to, any one of 0.77 dL / g, 0.78 dL / g, 0.79 dL / g, 0.80 dL / g, 0.81 dL / g, 0.82 dL / g, 0.83 dL / g, 0.84 dL / g, 0.85 dL / g, 0.86 dL / g, 0.87 dL / g, 0.88 dL / g, 0.89 dL / g, 0.90 dL / g or a range between any two of them. Optionally, the size of the bottle flakes is 12 mm×12 mm. Optionally, the mass proportion of the bottle flakes in the first component is greater than or equal to 70 wt%.
[0058] In some embodiments, the mass ratio of the first component to the second component is (40-50):(60-50). Optionally, the mass ratio of the first component to the second component is 50:50.
[0059] In some embodiments, the first component includes a first recycled polyester and an elastomer, and in the first component, the mass ratio of the first recycled polyester to the elastomer is (60-99):(40-1). It can be understood that the mass of the first recycled polyester in the first component is greater than the mass of the elastomer. By adding the elastomer to the first recycled polyester, the elastomer can recover its deformation property to increase the elongation of the first component when subjected to force, thereby improving its elasticity. As an example, the mass ratio of the first recycled polyester to the elastomer can be, for example, but not limited to, any one of 9:1, 8:2, 7:3, 6:4, or a range between any two of the ratios.
[0060] In some embodiments, the elastomer includes at least one of thermoplastic polyurethane (TPU), polyethylene-polyvinyl acetate elastomer, polyethylene terephthalate-1,4-cyclohexanedimethanol ester (PETG), polyethylene terephthalate-polyethylene glycol (PET-PEG) block copolymer, and polyamide elastomer (TPAE). Optionally, the elastomer includes PETG and / or PET-PEG block copolymer, and PETG and / or PET-PEG block copolymer is obtained based on waste polyester material through chemical regeneration method. Since PETG and PET-PEG block copolymers are similar to polyester structures and can be blended with R-PET in any proportion, if PETG and PET-PEG block copolymers obtained based on waste polyester material through chemical regeneration method are introduced as elastomers, it is possible to reduce processing difficulty, reduce production costs, broaden the application prospects of waste polyester materials, and promote the sustainable development of the industrial chain.
[0061] In some embodiments, the elastomer includes at least one of a styrene-based thermoplastic elastomer (TPR) and a thermoplastic polyolefin elastomer (TPO). Optionally, the elastomer includes a polyolefin elastomer, which includes but is not limited to ethylene-propylene copolymer (PBE). Since the permanent deformation of polyolefin elastomers is small, the durability of the parallel composite fiber can be further improved by introducing the polyolefin elastomer into the first component, thereby extending the service life of the parallel composite fiber.
[0062] In some embodiments, the elastomer includes PETG and PET-PEG block copolymers, and the mass ratio of PET-PEG block copolymer to PETG is (0.05-0.4). As an example, the mass ratio of PET-PEG block copolymer to PETG can be, for example but not limited to, any one of 0.05, 0.1, 0.15, 0.2, 0.25, 0.3, 0.35, 0.4 or a range between any two of them. Optionally, the polyester component in PETG and PET-PEG block copolymers is PET obtained by chemical regeneration of waste polyester materials.
[0063] In some embodiments, the first component further includes a compatibilizer, and the amount of the compatibilizer added is 1wt% to 10wt% of the total mass of the first component. As an example, the amount of the compatibilizer added can be, for example, but not limited to, any one of 1wt%, 2wt%, 3wt%, 4wt%, 5wt%, 6wt%, 7wt%, 8wt%, 9wt%, 10wt% or a range between any two of them. It can be understood that the first component includes a first recycled polyester, an elastomer and a compatibilizer. As an example, in the first component, the mass ratio of the first recycled polyester, the elastomer and the compatibilizer can be, for example, but not limited to, any one of 90:9:1, 80:18:2, 70:27:3, and 60:36:4.
[0064] In some embodiments, the compatibilizer is prepared by grafting a grafted monomer with a polyolefin or a polyolefin elastomer. Optionally, the grafted monomer includes at least one of maleic anhydride and glycidyl methacrylate (GMA). Optionally, the compatibilizer is prepared by grafting a grafted monomer with a polyethylene obtained by recycling waste bottle caps. Optionally, the polyolefin includes but is not limited to polyethylene and / or polypropylene. Optionally, the polyolefin elastomer includes but is not limited to polypropylene and polybutylene.
[0065] In some embodiments, the second component includes a second recycled polyester and a nucleating agent, and in the second component, the mass proportion of the nucleating agent is 0.1wt% to 3wt%. By adding a nucleating agent in this ratio range to the second component, the crystallinity of the second recycled polyester with a relatively high viscosity can be increased, and its rigidity can be improved, thereby increasing the difference between the first component and the second component, increasing the bending tendency of the prepared parallel composite fiber, strengthening the resilience of the three-dimensional curling structure, and improving the curling degree, curl recovery rate and curl elastic modulus of the fiber. As an example, the mass proportion of the nucleating agent in the second component can be, for example, but not limited to, any one of 1wt%, 2wt%, 3wt% or a range value between any two.
[0066] In some embodiments, the nucleating agent is an inorganic nucleating agent. Adding an inorganic nucleating agent to the second component can improve the crystallization speed and uniformity of the second recycled polyester with a relatively high viscosity in the second component, thereby obtaining smaller and more uniform spherulites. The small grains make the grain boundaries inside the fiber more numerous and tortuous, and can effectively prevent the propagation of cracks when subjected to force, so that the material can withstand greater plastic deformation before breaking, absorb more energy, show better plasticity and toughness, and increase the durability of the product. At the same time, when an inorganic nucleating agent is added to the second component, the inorganic nucleating agent will not react chemically with the polymer like an organic nucleating agent, causing the PET molecular chain to break and the molecular weight to decrease, thereby causing the PET to be easily degraded, and ultimately affecting the mechanical strength of the product. Optionally, the second component includes a second recycled polyester and an inorganic nucleating agent, and the crystallinity of the second component at room temperature is 40% to 50%.
[0067] In some embodiments, the inorganic nucleating agent includes at least one of ZnO, MgO, Al2O3, Fe2O3, SiO2, BaSO4, Na2CO3, NaHCO3, CaCO3, carbon black, graphite, zinc powder, aluminum powder, talc, halloysite, carbon nanotubes, montmorillonite, metal-organic framework materials (MOF) and pyrophyllite.
[0068] In some embodiments, the morphology of the inorganic nucleating agent includes at least one of a tube, a rod, a plate, a spiral, and a particle.
[0069] In some embodiments, the particle size of the inorganic nucleating agent is 450 nm to 550 nm. Alternatively, the particle size of the inorganic nucleating agent is 500 nm.
[0070] In some embodiments, the MOF includes at least one of ZIF-8, ZIF-67, MIL-53, MIL-100, and MIL-101. Optionally, the coordination metal of ZIF-8 is Zn, the ligand is 2-methylimidazole, and the molecular formula is C8H 10N4Zn. Optionally, the coordination metal of ZIF-67 is Co, the ligand is 2-methylimidazole, and the molecular formula is C8H 12 N4Co. Optionally, the coordination metal of MIL-53 is Fe, the ligand is terephthalic acid, and the molecular formula is C8H4FeO5. Optionally, the coordination metal of MIL-100 is Fe, the ligand is trimesic acid, and the molecular formula is C9H6O6Fe. Optionally, the coordination metal of MIL-101 is Cr, the ligand is terephthalic acid, and the molecular formula is C 24 H 16 Cr3FO 15 .
[0071] In some embodiments, the second component also includes an ionic liquid, which is adsorbed on the nucleating agent, and the amount of the ionic liquid added is 0.1wt% to 5wt% of the total mass of the nucleating agent. Ionic liquid refers to a liquid composed entirely of ions. Ionic liquids are generally composed of organic cations and inorganic or organic anions. After the ionic liquid is adsorbed on the nucleating agent, it can effectively prevent the nucleating agent from agglomerating, and because the ionic liquid has a strong polarity, it further improves the dispersibility of the nucleating agent in the polymer, making the nucleating agent more evenly dispersed in the material, and the resulting grains are finer, and the toughness and durability of the product are better. As an example, the amount of ionic liquid added can be, for example, but not limited to, any one of 0.1wt%, 0.5wt%, 1wt%, 1.5wt%, 2wt%, 2.5wt%, 3wt%, 3.5wt%, 4wt%, 4.5wt%, 5wt% or any range between two values.
[0072] In some embodiments, the ionic liquid includes at least one of 1-allyl-3-methylimidazole chloride, 1-butyl-4-methylpyridinium hexafluorophosphate, 2-methylimidazole, 2-bromoisobutyryl bromide, N-butyl-4-methylpyridinium hexafluorophosphate, 1-tetradecyl-3-methylimidazole bromide, and 1-dodecyl-3-methylimidazole chloride.
[0073] A second aspect of the present application provides a method for preparing the above-mentioned parallel composite fiber, the method comprising:
[0074] S1: providing a premix of a first component, and subjecting the premix of the first component to a melt extrusion process to obtain a first melt;
[0075] S2: providing a premix of a second component, and subjecting the premix of the second component to melt extrusion to obtain a second melt;
[0076] S3: subjecting the first melt and the second melt to composite spinning to obtain parallel composite fiber precursors;
[0077] S4: post-treating the parallel type composite fiber precursor to obtain the parallel type composite fiber.
[0078] In the preparation method of the parallel composite fiber provided in the second aspect of the embodiment of the present application, the first component includes a first recycled polyester and an elastomer; the second component includes a second recycled polyester and a nucleating agent; the first component and the second component are subjected to a composite spinning process to obtain a composite fiber with a parallel structure. The embodiment of the present application specifically adds an elastomer to the first component to improve its elasticity, adds a nucleating agent to the second component to improve its rigidity, increases the difference between the two components, and strengthens the three-dimensional curling resilience of the parallel composite fiber, so that the fiber has good breaking strength and breaking elongation, and the curling elasticity is generally above 80%, and has the characteristics of good fluffiness, washability and durability.
[0079] In some embodiments, the composite spinning process includes: metering the first melt and the second melt separately and entering the spinning assembly for spinning, and ejecting through the parallel composite spinning assembly. Optionally, in the spinning assembly, the viscosity ratio of the first melt to the second melt is 1:(1 to 1.2). As an example, the viscosity ratio of the first melt to the second melt can be, for example but not limited to, any one of 1:1.01, 1:1.03, 1:1.06, 1:1.09, 1:1.12, 1:1.15, 1:1.17, 1:1.19 or a range between any two of them.
[0080] In some embodiments, post-processing includes: spraying water mist, cooling with ring air, oiling and stretching the parallel composite fiber precursor to make primary fibers, and then bundling, post-stretching, curling, shaping and cutting to make parallel composite fibers.
[0081] In some embodiments, the spray speed of the water mist spray is 3.8m / s to 4.0m / s, and the water temperature is 24°C to 26°C. As an example, the spray speed of the water mist spray can be, for example but not limited to, any one of 3.8m / s, 3.85m / s, 3.9m / s, 3.95m / s, 4.0m / s, or a range between any two of them. As an example, the water temperature can be, for example but not limited to, any one of 24°C, 24.5°C, 25°C, 25.5°C, 26°C, or a range between any two of them.
[0082] In some embodiments, the annular wind speed of the annular wind cooling is 2.0m / s to 2.8m / s, and the wind temperature is controlled at 21°C to 23°C. As an example, the annular wind speed can be, for example but not limited to, any one of 2.0m / s, 2.1m / s, 2.2m / s, 2.3m / s, 2.4m / s, 2.5m / s, 2.6m / s, 2.7m / s, and 2.8m / s, or a range between any two of them. As an example, the wind temperature can be, for example but not limited to, any one of 21°C, 21.5°C, 22°C, 22.5°C, and 23°C, or a range between any two of them. By adjusting the cooling conditions, changing the crystal size of PET in the second component, adjusting the difference in thermal shrinkage between the first component and the second component, and thus achieving the purpose of controlling the fiber curl.
[0083] In some embodiments, the post-stretching drawing speed is 200 m / min to 240 m / min. As an example, the drawing speed can be, for example but not limited to, any one of 200 m / min, 210 m / min, 220 m / min, 230 m / min, 240 m / min, or a range between any two of them.
[0084] In some embodiments, the winding speed of the winding is 1300 m / min to 1700 m / min. As an example, the winding speed of the winding can be, for example but not limited to, any one of 1300 m / min, 1400 m / min, 1500 m / min, 1600 m / min, 1700 m / min or a range between any two thereof.
[0085] In some embodiments, the premix of the first component or the second component is melt-extruded by a screw extruder, wherein the temperature of the screw barrel heating zone of the screw extruder is 285° C. to 340° C. As an example, the temperature of the screw barrel heating zone can be, for example but not limited to, any one of 285° C., 290° C., 300° C., 310° C., 320° C., 330° C., 340° C. or a range between any two of them.
[0086] The following describes the invention in conjunction with specific embodiments.
[0087] Example 1
[0088] This example provides a method for preparing a high elastic filling composite fiber based on R-PET. The method uses R-PET with different viscosities obtained from different recycling sources as raw materials and uses a parallel composite spinning assembly to prepare a two-component parallel composite fiber with a parallel structure. The method includes the following steps:
[0089] Step 1: low viscosity R-PET is mixed with an elastomer and a compatibilizer in a mass ratio of 90:9:1 to obtain a premix of the first component; then the first component is added into a screw extruder and the melt after melt extrusion enters a spinning manifold A.
[0090] The low-viscosity R-PET part is composed of PET bottle flakes and PET friction material. The intrinsic viscosity of PET bottle flakes is 0.78dL / g, the size is 12mm×12mm, accounting for 70% of the mass of R-PET. The intrinsic viscosity of PET friction material is 0.65dL / g, the size is 12mm×6mm, accounting for 30% of the mass of R-PET. The elastomer is ethylene-propylene copolymer (PBE), the melt index is 6000g / 10min, and the density is 0.861g / cm 3 , Vicat softening point is 48°C, of which ethylene accounts for 15wt% of the total mass; the compatibilizer is prepared by polyethylene grafted with maleic anhydride obtained by recycling waste bottle caps.
[0091] Specifically, the premixing process is: adding PET bottle flakes, PET friction material and ethylene-propylene copolymer into a high-speed mixer with a rotation speed of 1500 r / min according to a proportion, mixing for 18 minutes, and obtaining a premix.
[0092] The processing temperature of the screw extruder was controlled at 275°C; the screw speed of the screw extruder was 150 r / min.
[0093] Step 2: High-viscosity R-PET and the nucleating agent treated with ionic liquid surface are mixed in a mass ratio of 99:1 to obtain a premix of the second component; then the second component is added into the screw extruder and the melt after melt extrusion enters the spinning box B.
[0094] Among them, the high-viscosity R-PET part is bottle flakes recycled from waste PET bottles or solid-phase thickening material of bottle flakes, with a characteristic viscosity of 0.71dL / g; the nucleating agent is halloysite, and the particle size is 500nm.
[0095] Specifically, the surface treatment process of the inorganic nucleating agent is as follows: take 1g of 1-allyl-3-methylimidazole chloride and ultrasonicate it in an ultrasonic oscillator for 30 minutes, then weigh 50g of halloysite and put it into a three-necked flask, then add the ultrasonicated 1-allyl-3-methylimidazole chloride, and then add 200mL of anhydrous ethanol, stir in a constant temperature water bath at 60°C for 2h, then serve, and dry in a vacuum drying oven at 90°C for 12h to obtain the surface-treated halloysite, serve and seal it for standby use.
[0096] The premixing process is as follows: R-PET and surface-treated halloysite are added into a high-speed mixer at a rotation speed of 2000 r / min according to a proportion, and mixed for 20 minutes to obtain a premix.
[0097] The processing temperature of the screw extruder was controlled at 265°C; the screw speed of the screw extruder was 175 r / min.
[0098] Step 3:
[0099] The melts in the spinning boxes A and B are respectively metered and enter the spinning assembly, and are ejected from the parallel composite spinneret assembly to obtain parallel composite fiber precursors; they are then subjected to water mist spraying, annular air cooling, oiling and stretching to form primary fibers, and then subjected to bundling, post-stretching, curling, shaping and cutting to form high-elastic filling composite fibers based on R-PET.
[0100] Among them, the mass ratio of the first component in box A to the second component in box B in the fiber precursor is 50:50; the water mist spray speed is 3.8m / s, the water temperature is 25±1℃, the ring blowing speed is 2.3m / s, and the wind temperature is controlled at 22±1℃; the drawing speed is 220m / min, and the spinning winding speed is 1500m / min.
[0101] Embodiment 2~3:
[0102] Examples 2 to 3 provide a method for preparing a high-elastic filling composite fiber based on R-PET. The only difference between this method and Example 1 is the different formula of the second component. In Examples 2 to 3, halloysite accounts for 2wt% and 3wt% of the total mass of the second component, respectively.
[0103] Embodiment 4~6:
[0104] Examples 4 to 6 provide a method for preparing a highly elastic filling composite fiber based on R-PET. The only difference between this method and Example 1 is the different formula. In Examples 4 to 6, the mass ratio of R-PET to PBE elastomer and its compatibilizer in the first component is 80:18:2, and the halloysite in the second component accounts for 1wt%, 2wt% and 3wt% of the total mass of the second component, respectively.
[0105] Embodiment 7~9:
[0106] Examples 7 to 9 provide a method for preparing a highly elastic filling composite fiber based on R-PET. The only difference between this method and Example 1 is the different formula. In Examples 7 to 9, the mass ratio of R-PET to PBE elastomer and its compatibilizer in the first component is 70:27:3, and the halloysite in the second component accounts for 1wt%, 2wt% and 3wt% of the total mass of the second component, respectively.
[0107] Embodiments 10 to 12:
[0108] Examples 10 to 12 provide a method for preparing a highly elastic filling composite fiber based on R-PET. The only difference between this method and Example 1 is the different formula. In Examples 10 to 12, the mass ratio of R-PET to PBE elastomer and its compatibilizer in the first component is 60:36:4, and the halloysite in the second component accounts for 1wt%, 2wt% and 3wt% of the total mass of the second component, respectively.
[0109] Embodiments 13 to 15:
[0110] The only difference between Examples 13 to 15 and Example 1 is the different formulas. In Examples 13 to 15, the mass ratio of R-PET to PBE elastomer and its compatibilizer in the first component is 80:18:2, and the nucleating agent in the second component is changed to montmorillonite, accounting for 1wt%, 2wt% and 3wt% of the total mass of the second component, respectively.
[0111] Embodiments 16 to 19:
[0112] The only difference between Examples 16 to 19 and Example 1 is that the formula is different. In Examples 16 to 19, the elastomer in the first component is changed to PETG elastomer, and the mass ratios of R-PET to PETG elastomer are 9:1, 8:2, 7:3 and 6:4, respectively. The halloysite in the second component accounts for 2% of the total mass of the second component.
[0113] Comparative Example 1:
[0114] The low-viscosity R-PET and the high-viscosity R-PET were respectively mixed with the nucleating agent surface-treated with ionic liquid in a mass ratio of 99:1 to obtain a first component and a second component, and then the first component and the second component were added into a screw extruder, and the melts after melt extrusion entered the spinning manifold A and the spinning manifold B respectively, and entered the spinning assembly after metering, and after being ejected from the parallel composite spinneret assembly, parallel composite fiber precursors were obtained, and primary fibers were prepared through water mist spraying, annular air cooling, oiling and stretching, and then through bundling, post-stretching, curling, shaping and cutting to prepare high-elasticity filling composite fibers based on R-PET.
[0115] The low-viscosity R-PET, high-viscosity R-PET, halloysite, blending method, and spinning process used are the same as those in Example 1.
[0116] Comparative Examples 2-3:
[0117] The difference between Comparative Examples 2 and 3 and Comparative Example 1 is only the different contents of halloysite. In Examples 2 and 3, the halloysite accounts for 2% and 3% of the total mass, respectively.
[0118] Comparative Example 4:
[0119] Low-viscosity R-PET and high-viscosity R-PET are added to an elastomer and a compatibilizer at a mass ratio of 90:9:1 and mixed to obtain a first component and a second component. The first component and the second component are then added to a screw extruder, and the melts after melt extrusion enter spinning manifold A and spinning manifold B respectively, and enter the spinning assembly after metering. After being ejected from the parallel composite spinneret assembly, parallel composite fiber precursors are obtained, which are made into primary fibers through water mist spraying, annular air cooling, oiling and stretching, and then made into high-elastic filling composite fibers based on R-PET through bundling, post-stretching, curling, shaping and cutting.
[0120] The low-viscosity R-PET, high-viscosity R-PET, elastomer and its compatibilizer, blending method, and spinning process used are the same as those in Example 1.
[0121] Comparative Examples 5 to 7:
[0122] The difference between Comparative Examples 5 to 7 and Comparative Example 4 is only the different content of the elastomer. The mass ratios of R-PET to PBE elastomer and its compatibilizer in Examples 5 to 7 are 80:18:2, 70:27:3 and 60:36:4, respectively.
[0123] In order to verify the progressiveness of the present application, performance tests were carried out on the fibers prepared in the comparative example and the fibers prepared in the examples, wherein the breaking strength and breaking elongation of the fibers prepared in the comparative example and the fibers prepared in the examples were tested with reference to GB / T 14460-2015, and the curl number, curl degree, curl recovery rate and curl elastic modulus were all tested with reference to GB / T14338-2008.
[0124] Table 1 Performance test results
[0125]
[0126] According to Table 1, the breaking strength of the parallel composite fibers prepared in Examples 1 to 19 is 2.7 to 3.2 cN / tex, the breaking elongation is 30% to 212%, the number of crimps is (10 to 17) pieces / 25 mm, the crimp degree is 11% to 16%, the crimp recovery rate is 10% to 15%, and the crimp elasticity is 80% to 90%. Compared with the comparative example, the crimping effect is improved.
[0127] Examples 1 to 3 are a group of examples. The difference between the examples in this group lies in the different formulations of the second component. Specifically, the mass proportion of the nucleating agent halloysite in Examples 1 to 3 increases successively, which are 1wt%, 2wt% and 3wt%, respectively. It can be seen from Table 1 that as the content of the nucleating agent increases, the curling effect improves.
[0128] The difference between Examples 1 to 3, Examples 4 to 6, Examples 7 to 9 and Examples 10 to 12 is that the mass ratio of R-PET to PBE elastomer and its compatibilizer in the first component changes to 90:9:1, 80:18:2, 70:27:3, and 60:36:4, respectively. The content of R-PET decreases, and the content of elastomer and its compatibilizer increases. It can be seen from Table 1 that as the content of elastomer and its compatibilizer increases, the curling effect increases, but the breaking strength decreases.
[0129] Examples 13 to 15 correspond to Examples 4 to 6, except that the nucleating agent in the second component is changed to montmorillonite. As can be seen from Table 1, the fibers prepared in Examples 13 to 15 also have better curling effect and strength.
[0130] Examples 16 to 19 correspond to Examples 2, 5, 8, and 11, and the only difference is the formula. Specifically, the elastomer in the first component is changed to PETG elastomer. As can be seen from Table 1, the fibers prepared in Examples 16 to 19 also have better curling effect and strength.
[0131] Comparative Examples 1 to 3 correspond to Examples 1 to 3, except that no elastomer is added. As shown in Table 1, the curling effect of the fibers prepared in Comparative Examples 1 to 3 is not as good as that of the fibers prepared in Examples 1 to 3.
[0132] Comparative Example 4 corresponds to Example 1, except that no nucleating agent is added. As can be seen from Table 1, the curling effect of the fiber prepared in Comparative Example 4 is not as good as the curling effect of the fiber prepared in Example 1.
[0133] Comparative Examples 5 to 7 correspond to Comparative Example 4, except that the mass ratios of R-PET to PBE elastomer and its compatibilizer are 80:18:2, 70:27:3 and 60:36:4, respectively. As can be seen from Table 1, no nucleating agent is added, and even if the content of the elastomer is increased, the curling effect is not improved.
[0134] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present application should be included in the protection scope of the present application.
Claims
1. A side-by-side composite fiber, characterized in that: include: A first component and a second component, wherein the first component comprises a first recycled polyester and an elastomer, and the second component comprises a second recycled polyester and a nucleating agent, and under the same conditions, the viscosity of the melt of the first recycled polyester is lower than the viscosity of the melt of the second recycled polyester; The intrinsic viscosity of the first recycled polyester is 0.65 dL / g to 0.75 dL / g; The intrinsic viscosity of the second recycled polyester is 0.67 dL / g to 0.80 dL / g; The first recycled polyester includes at least one of bottle flakes obtained from waste PET bottles, friction materials obtained from waste PET films, waste PET yarns, waste PET textiles or / and waste PET clothing, and foam materials obtained from waste PET films, waste PET sheets, waste PET yarns, waste PET textiles or / and waste PET clothing; The second recycled polyester includes bottle flakes and / or solid phase viscosity-increasing materials of bottle flakes obtained by recycling waste PET bottles; The mass ratio of the first component to the second component is (40-50):(60-50); In the first component, the mass ratio of the first recycled polyester to the elastomer is (60-99):(40-1); The elastomer includes at least one of styrene-based thermoplastic elastomer, thermoplastic polyurethane, thermoplastic polyolefin elastomer, polyethylene-polyvinyl acetate elastomer, polyamide elastomer, polyethylene terephthalate-polyethylene glycol block copolymer, and polyethylene terephthalate-1,4-cyclohexanedimethanol ester; The first component further includes a compatibilizer, the addition amount of the compatibilizer is 1wt% to 10wt% of the total mass of the first component, the compatibilizer is prepared by grafting a grafting monomer of a polyolefin or a polyolefin elastomer, and the grafting monomer includes at least one of maleic anhydride and glycidyl methacrylate (GMA); In the second component, the mass proportion of the nucleating agent is 0.1wt%~3wt%; The nucleating agent is an inorganic nucleating agent, and the inorganic nucleating agent includes at least one of ZnO, MgO, Al2O3, Fe2O3, SiO2, BaSO4, Na2CO3, NaHCO3, CaCO3, carbon black, graphite, zinc powder, aluminum powder, talcum powder, halloysite, carbon nanotubes, montmorillonite, metal-organic framework materials and pyrophyllite; The second component also includes an ionic liquid, which is adsorbed on the nucleating agent. The added amount of the ionic liquid is 0.1wt%~5wt% of the total mass of the nucleating agent, and the ionic liquid includes at least one of 1-allyl-3-methylimidazole chloride, 1-butyl-4-methylpyridinium hexafluorophosphate, 2-methylimidazole, 2-bromoisobutyryl bromide, N-butyl-4-methylpyridinium hexafluorophosphate, 1-tetradecyl-3-methylimidazole bromide, and 1-dodecyl-3-methylimidazole chloride.
2. The side-by-side composite fiber according to claim 1, wherein The elastomer includes the polyethylene terephthalate-1,4-cyclohexanedimethanol ester and the polyethylene terephthalate-polyethylene glycol block copolymer, and the mass ratio of the polyethylene terephthalate-polyethylene glycol block copolymer to the polyethylene terephthalate-1,4-cyclohexanedimethanol ester is (0.05-0.4).
3. The side-by-side composite fiber according to claim 1 or 2, characterized in that: The morphology of the inorganic nucleating agent includes at least one of tubular, rod-shaped, sheet-shaped, spiral-shaped and granular; And / or, the particle size of the inorganic nucleating agent is 450nm~550nm; And / or, the metal-organic framework material includes at least one of ZIF-8, ZIF-67, MIL-53, MIL-100 and MIL-101.
4. The method for preparing the side-by-side composite fiber according to any one of claims 1 to 3, characterized in that: include: Providing a premix of the first component, and subjecting the premix of the first component to melt extrusion to obtain a first melt; Providing a premix of the second component, and subjecting the premix of the second component to melt extrusion to obtain a second melt; The first melt and the second melt are subjected to composite spinning to obtain parallel composite fiber precursors; The parallel type composite fiber precursor is post-processed to obtain the parallel type composite fiber.
5. The method for preparing the side-by-side composite fiber according to claim 4, characterized in that: The composite spinning process includes: metering the first melt and the second melt separately and entering the spinning assembly for spinning, and ejecting them through a parallel composite spinneret assembly; wherein, in the spinning assembly, the viscosity ratio of the first melt to the second melt is 1: (1~1.2).
6. The method for preparing the side-by-side composite fiber according to claim 4, characterized in that: The post-treatment includes: spraying the parallel composite fiber precursor with water mist, cooling with ring air, oiling and stretching to make primary fibers, and then bundling, post-stretching, curling, shaping and cutting to make the parallel composite fiber.
7. The method for preparing the side-by-side composite fiber according to claim 6, characterized in that: The spray speed of the water mist spray is 3.8 m / s to 4.0 m / s, and the water temperature is 24°C to 26°C; And / or, the annular air cooling has an annular air speed of 2.0 m / s to 2.8 m / s, and an air temperature of 21° C. to 23° C.; And / or, the post-stretching drafting speed is 200 m / min to 240 m / min; And / or, the curling spinning winding speed is 1300 m / min ~1700 m / min.
Citation Information
Patent Citations
Polyester composite fiber and woven knit containing polyester composite fiber
JP2021155901A
Polyester bicomponent filament
US20040099984A1